Perancangan Sistem Hidrolik pada Unit Mobile Core Sampler - Fitria Adhi Geha Nusa; Sugiyanto Sugiyanto (Jurnal Nasional Teknologi Terapan (JNTT), 2017)
Sugarcane core sampler is a plantation equipment sector which collect sugar cane samples and determining of rendemen in sugarcane. Sugarcane core sampler is a new product made by PT. United Tractors Pandu Engineering to solve problem about determining of individual rendemen in sugarcane at sugar mill. In operation Sugarcane Core Sampler uses a hydraulic system as the prime mover, either to raise the platform, take samples of cane and push it out of the probe cylinder. In order for the hydraulic system to work optimally, it is necessary to design and calculate the specification of components to be used on tilting cylinders, ejector, hydraulic pump, and reservoir (hydraulic tank). It also conducted a discussion of the difference between the Core Sampler Sugarcane fixed and mobile models. From the calculation results obtained inside diameter tilting cylinder is Ø100 mm with rod cylinder Ø56 mm, inside diameter of ejector cylinder is Ø32 mm with rod cylinder Ø1 8mm. At the biggest pump flow required is 51.81 lpm and displacement 43 cc/rev, from result of calculation hence specified pump which used is pist on pump type with displacement 41 cc/rev. For hydraulic tank capacity requiredon all hydraulic systems is 177 liters.